C+2(d-5c)=

Simple and best practice solution for C+2(d-5c)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for C+2(d-5c)= equation:


Simplifying
C + 2(d + -5c) = 0

Reorder the terms:
C + 2(-5c + d) = 0
C + (-5c * 2 + d * 2) = 0
C + (-10c + 2d) = 0

Solving
C + -10c + 2d = 0

Solving for variable 'C'.

Move all terms containing C to the left, all other terms to the right.

Add '10c' to each side of the equation.
C + -10c + 10c + 2d = 0 + 10c

Combine like terms: -10c + 10c = 0
C + 0 + 2d = 0 + 10c
C + 2d = 0 + 10c
Remove the zero:
C + 2d = 10c

Add '-2d' to each side of the equation.
C + 2d + -2d = 10c + -2d

Combine like terms: 2d + -2d = 0
C + 0 = 10c + -2d
C = 10c + -2d

Simplifying
C = 10c + -2d

 

See similar equations:

| 13x-4=9x-20 | | 50=x+7x+10 | | 6=6-4t-7t | | 0.05m-0.001=0.73m+1.9 | | -4+9=1 | | 8+8+x+x=28 | | 6x+2=x-7 | | -3=5-y-y | | -9z=-873 | | 11x-2+75=180 | | 4x^2-4x+1=1 | | 3x-16=-x-16 | | 8x-4(2-x)=6x+19+6x | | -20x+7y=137 | | 1x+10y=163 | | -3x^2+147=0 | | 10=j+9 | | 30u=240 | | 600x+200=500x | | 8x-4+60=180 | | 15x-18-2y=3x+y | | =5x-3[10x-4y] | | 18X-1=12X-13 | | x+24+x=28 | | 168=k+9 | | 3a+2b-3a+1-3= | | 3z-10=5x+6 | | 6x^2+13x+7= | | 40-7x=-5(4x+5) | | 5(4x+1)=3x-7x | | 8abs(9x-5)=6abs(9x-5) | | 3x+16=-x-16 | | 7(2x)=15 | | 5-n=4+6n | | -4z-5z=9z-5-8z | | x^2-26x+184=51 | | 3(4x)+(4x)= | | -12+15=-3(x+5) | | 7+1(2x)=15 | | Y=-x^2+9 | | -53+-2i=-i+20 | | 3a-3a= | | fx+74=12x+14 | | -3y-15=4y+20 | | 5-7[2-(4x+3)]=0 | | 7(y-1)=3y+9 | | 69=x-0.23x | | 6(4x-7)=24x-42 | | 5z-4(2-9)=4+2z | | -4x+9=1 | | 28=8x-4 | | 5(2b-4)=4(5b-3) | | 4x+26=11x-30 | | -37-n=6(-2n-8) | | 3(4x+6)=12x+18 | | 3x+4=3(x+6) | | 5(2-t)-(2-3t)=1 | | 8x-3=8(x-3) | | 0.4(15y+10)-2(4y+3)=0 | | 6-3(4-x)=2x-1 | | 33=-7x-9 | | -4(2x-6)+3=-8x+27 | | 3x+5=2x-3 | | 5-6x+x=30 | | 75-4x=8x+15 |